2020
DOI: 10.3889/oamjms.2020.3684
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Case of Intestinal Obstruction from Internal Hernia through a Foramen Formed by Appendices Epiploicae – A Case Report and Review of Literature

Abstract: BACKGROUND: Internal hernias are uncommon causes of acute abdomen and intestinal obstruction. Internal herniation due to appendices epiploicae is very rare with only six cases reported in the literature.CASE REPORT: We, herein, present the report of a 64-year-old female who presented with features of intestinal obstruction due to internal herniation of a loop of small intestine through an orifice formed by the fusion of two appendices epiploicae. The band was divided into release the entrapped loop of bowel.CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The second case was reported 13 years later, after the report of the first case by Krijgsman and Salter 12 at Westcliff‐On‐Sea, Essex, United Kingdom. The other five studies are available through the literature, 6 , 7 , 8 , 9 , 10 as the two most recent were published in 2018 13 and 2020. 7 Butt et al 14 also reported another case of SBO due to the entrapment of a small bowel loop between two inflamed epiploic appendices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second case was reported 13 years later, after the report of the first case by Krijgsman and Salter 12 at Westcliff‐On‐Sea, Essex, United Kingdom. The other five studies are available through the literature, 6 , 7 , 8 , 9 , 10 as the two most recent were published in 2018 13 and 2020. 7 Butt et al 14 also reported another case of SBO due to the entrapment of a small bowel loop between two inflamed epiploic appendices.…”
Section: Discussionmentioning
confidence: 99%
“…The other five studies are available through the literature, 6 , 7 , 8 , 9 , 10 as the two most recent were published in 2018 13 and 2020. 7 Butt et al 14 also reported another case of SBO due to the entrapment of a small bowel loop between two inflamed epiploic appendices. Their case was a 48‐year‐old man who presented with colicky abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation